Albumin Levels in Nontraumatic Acute Abdomen Patients Undergoing Emergency Laparotomy: A Retrospective Study in the Intensive Observation Ward of Dr. Soetomo General Academic Hospital - Fitri mazia; Maulydia; Edwin Danardono; Edward Kusuma (Indonesian Journal of Anesthesiology and Reanimation, 2025)
Introduction: Acute abdomen is a critical medical emergency characterized by the abrupt onset of severe abdominal pain, often requiring emergency laparotomy. Emergency laparotomy, due to limited preoperative preparation, generally has a higher morbidity and mortality rate than elective surgery. Optimizing perioperative care, particularly by monitoring albumin levels, may improve outcomes, as albumin plays a crucial role in maintaining fluid balance, wound healing, and controlling inflammatory responses. Postoperative emergency patients at Dr. Soetomo General Academic Hospital are closely monitored in a specific ward known as the Intensive Observation Ward (Ruang Observasi Intensif/ROI). Objective: To evaluate albumin levels in nontraumatic acute abdomen patients treated in ROI following emergency laparotomy. Methods: This study used a retrospective descriptive study design and was conducted from January to June 2022. Patients under 18 with malignancy, trauma, gynecological or obstetrical cases, and incomplete medical records were excluded. Results: The male and female number of 90 patients was equal, most patients were aged 41-50, and had a normal BMI. Generalized peritonitis was the most common indication, followed by acute appendicitis and bowel obstruction. Appendectomy and exploratory laparotomy were the primary procedures, mostly done in under 3 hours. Most patients had no prior laparotomy history. Most patients had normal albumin levels preoperatively, but these shifted to mild hypoalbuminemia postoperatively. Of 13 deaths, 12 involved preoperative hypoalbuminemia. The predominant PS-ASA scores were 2 and 3. Electrolyte imbalance, especially hypokalemia, was the prevalent preoperative complication. Frequent comorbidities included kidney disorders and hypertension. The average ROI stay was 2.1±1.59 days, with most patients staying for 1 to 3 days. Operation-related complications included intra-abdominal infections and bleeding, while medical complications involved electrolyte imbalances, sepsis, and metabolic acidosis. Conclusion: Nontraumatic acute abdomen patients with low preoperative albumin levels tend to have higher rates of postoperative complications and mortality.